Difference of Effectiveness Acarbose with Ethanol Extract Purple Eggplantâs Peel (Solanum melongena L) to Reduce Blood Sugar Levels in White Rat (Rattus norvegicus) Induced by Sucrose - Budianto, Nugroho Eko Wirawan; Hairullah, Hairullah (Universitas Wijaya Kusuma Surabaya, 2017)
Acarbose is an oligosaccharide human made who is a competitive inhibitor acarbose and can inhibit the action of the enzyme Î±-glucosidase, causing a slowdown in the digestion of carbohydrate compounds. Purple eggplant skin is included in the flavonoid compound. Purple eggplant Â skin as well as an antioxidant that can control blood glucose levels and prevent complications of diabetes. Purple eggplant skin contains flavonoid kaempferol and has the effect of inhibiting the enzyme alpha-glucosidase. Based on these researchers want to know the difference in effectiveness between the ethanol extract of purple eggplant skin Â and acarbose to decrease blood sugar levels of mice. The study population using white rats with a total sample size of 30 rats. Research data analysis using One Way Anova Test. Methods: Male rats strain Wistar were divided into 5 groups. 1) Control (CMC Na 1 ml io), 2) Group 1 Â (The ethanol extract of 50 mg / kg in the CMC Na io), Â 3) Group 2 Â (The ethanol extract 100 mg / kg in CMC Na io), 4) Group 3 Â (the ethanol extract 200 mg / kg in the CMC Na io), 5) Group 4 (Acarbose 4.5 mg / kg in distillated water io). The result showed ethanol extract of purple eggplant skin in group 2 showed the best effectiveness in lowering blood sugar levels of white rats by oral sucrose injection. And there is no significant difference between the effectiveness of the ethanol extract of purple eggplant skin and acarbose in lowering blood sugar levels of white rats by oral sucrose injection.